Piezo‐Photocatalysis over Metal–Organic Frameworks: Promoting Photocatalytic Activity by Piezoelectric Effect - Zhang, Chenxi; Lei, Da; Xie, Chenfan; Hang, Xiaoshuai; He, Chuanxin; Jiang, Hai‐Long (Advanced materials (Weinheim), 2021)
The built‐in electric field can be generated in the piezoelectric materials under mechanical stress. The resulting piezoelectric effect is beneficial to charge separation in photocatalysis. Meanwhile, the mechanical stress usually gives rise to accelerated mass transfer and enhanced catalytic activity. Unfortunately, it remains a challenge to differentiate the contribution of these two factors to catalytic performance. Herein, for the first time, isostructural metal–organic frameworks (MOFs), i.e., UiO‐66‐NH2(Zr) and UiO‐66‐NH2(Hf), are adopted for piezo‐photocatalysis. Both MOFs, featuring the same structures except for diverse Zr/Hf‐oxo clusters, possess distinctly different piezoelectric properties. Strikingly, UiO‐66‐NH2(Hf) exhibits ≈2.2 times of activity compared with that of UiO‐66‐NH2(Zr) under simultaneous light and ultrasonic irradiation, though both MOFs display similar activity in the photocatalytic H2 production without ultrasonic irradiation. Given their similar pore features and mass transfer behaviors, the activity difference is unambiguously assignable to the piezoelectric effect. As a result, the contributions of the piezoelectric effect to the piezo‐photocatalysis can be clearly distinguished owing to the stronger piezoelectric property of UiO‐66‐NH2(Hf). Two isostructural metal–organic frameworks (MOFs) with distinctly different piezoelectric responses are used in piezo‐photocatalysis. Remarkably, the H2 production efficiency of Hf‐MOF is 2.2 times that of Zr‐MOF under simultaneous light and ultrasonic irradiation. The role of the piezoelectric effect can be distinguished owing to their similar pore features and mass transfer behaviors.